Delivering insurance to protect livestock wealth and livelihoods in the drylands of Kenya - Bashir, H. (International Livestock Research Institute, 2016)
This filmed interview of Hassan Bashir, group chief executive of Takaful Africa Group, was prepared for the ILRI-World Bank Group side event at the Borlaug Dialogue, Des Moines, Iowa, 12 October 2016.